PENGARUH STRUKTUR MODAL, INVESTMENT OPPORTUNITY SET, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - DWI KURNIATI, TYAS; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to determine the effect of capital structure, investment opportunity set, and liquidity on firm value. Of the 43 companies in the banking sector there are 41 sample companies and will be analyzed from 2015 to 2017. This type of research uses a quantitative approach with multiple linear regression methods that are processed with SPSS version 22. The results show that the three variables both capital structure have a positive effect on firm value, investment opportunity set (IOS) has a positive effect on firm value and liquidity has a positive effect on firm value.